1992
DOI: 10.3171/jns.1992.76.2.0212
|View full text |Cite
|
Sign up to set email alerts
|

Continuous monitoring of jugular venous oxygen saturation in head-injured patients

Abstract: ✓ The continuous measurement of jugular venous oxygen saturation (SjvO2) with a fiberoptic catheter is evaluated as a method of detecting cerebral ischemia after head injury. Forty-five patients admitted to the hospital in coma after severe head injury had continuous and simultaneous monitoring of SjvO2, intracranial pressure, arterial oxygen saturation, and end-tidal CO2. Cerebral blood flow, cerebral metabolic rates of oxygen and lactate, arterial and jugular venous blood gas levels, and hemoglobin concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
23

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(129 citation statements)
references
References 15 publications
2
104
0
23
Order By: Relevance
“…The observation that bead-injured patients with cerebral venous desaturation had a higher mortality than those without such episodes highlights the potential benefit of detecting and treating such desaturation. 16 It would appear that the most important factor controlling cerebral blood flow (CBF) is PaCO2, as shown by the higher SjvO2, PjvO2 and CjvO2 at the higher PaCO2 of 30 mmHg (P < 0.01). Nonetheless, in the 12 patients studied, hyperoxygenation was beneficial in reducing the incidence of cerebral venous oxygen desaturation during hyperventilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that bead-injured patients with cerebral venous desaturation had a higher mortality than those without such episodes highlights the potential benefit of detecting and treating such desaturation. 16 It would appear that the most important factor controlling cerebral blood flow (CBF) is PaCO2, as shown by the higher SjvO2, PjvO2 and CjvO2 at the higher PaCO2 of 30 mmHg (P < 0.01). Nonetheless, in the 12 patients studied, hyperoxygenation was beneficial in reducing the incidence of cerebral venous oxygen desaturation during hyperventilation.…”
Section: Discussionmentioning
confidence: 99%
“…However, others have shown reductions in CBF with hyperoxia in normocapnic piglets, 13 ponies, 14 infants Is and adults. 16 This cerebral vasoconstriction may negate any potential beneficial effects of hyperoxia during hyperventilation. The effect of arterial hyperoxygenation on cerebral venous 0 2 content in anaesthetized patients during acute hyperventilation has not been fully investigated and is the purpose of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators using continuous jugular oxygen monitors have observed a significant association between episodes of jugular oxygen desaturation and poor outcome following head injury. [10,11,40,41,46] For example, Robertson, et al, [41] observed a 21% mortality rate in patients with no desaturation, 37% after a single episode, and 69% after multiple episodes. Poor outcome may also be associated with a reduced AVDO 2 , [21,40] because cerebral metabolism is significantly depressed once cerebral infarction has occurred.…”
Section: Arteriovenous Oxygen Difference and Outcomementioning
confidence: 99%
“…Although interpretation of SjVO 2 is based on several assumptions, a good correlation between SjVO 2 measured fiberoptically and via catheter has been observed. [46] Unfortunately, jugular saturation monitors require frequent recalibration and a high percentage of readings are erroneous because of catheter movement, displacement, intimal impaction, or clot formation. [14,46] Despite these limitations, jugular saturation monitoring can help guide therapy, optimize CPP, and measure the effects of therapeutic interventions, such as ventilation or mannitol administration, to ensure adequate CBF to meet metabolic demands.…”
Section: Applications For Jugular Oxygen Monitoringmentioning
confidence: 99%
“…Traditionally, electrophysiological monitoring [36] and measurement of oxygen saturation and lactate levels in jugular venous blood [37,38] have been used to monitor the adequacy of cerebral oxygen delivery; more recent studies have used the noninvasive technique of near-infrared spectroscopy of the brain [39].…”
Section: Tissue Oxygen Deliverymentioning
confidence: 99%